Value of magnetic resonance combined with dual-source spectral computed tomography in improving the clinical diagnosis and treatment efficiency of lumbar disk herniation - Ye,Chengbin (2021)
SUMMARY OBJECTIVE: This study aims to investigate the value of magnetic resonance combined with dual-source spectral computed tomography in improving the clinical diagnosis and treatment efficiency of lumbar disk herniation. METHODS: Two hundred patients with lumbar disk herniation were enrolled. Magnetic resonance and dual-source spectral computed tomography were used to perform the diagnosis. The treatment efficiency and effectiveness of different diagnostic methods were determined. Results: Eighty cases of lumbar disk herniation, 40 cases of prolapse, 33 cases of bulge, 27 cases of sequestration, and 20 cases of nodules were diagnosed based on pathologic evaluation. magnetic resonance detected lumbar disk herniation in 172 cases, with a detection rate of 86.00%. Dual-source spectral computed tomography detected 171 cases, with a detection rate of 85.50%. Magnetic resonance combined with dual-source spectral computed tomography detected 195 cases, with a detection rate of 97.50%. There was no significant difference between magnetic resonance and dual-source spectral computed tomography (p>0.05), but compared with the combined detection, there was a significant difference (p<0.05). One hundred and two cases of calcification, 83 cases of spinal cord deformity, 70 cases of intervertebral disk degeneration, 121 cases of intervertebral disk gas, 85 cases of dural sac compression, and 78 cases of nerve root compression were surgically demonstrated. The detection rate of diagnostic signs based on imaging by magnetic resonance or dual-source spectral computed tomography alone was lower than that of combined detection (p<0.05). Conclusion: Magnetic resonance combined with dual-source spectral computed tomography can improve the diagnosis and treatment efficiency and effectiveness of lumbar disk herniation.